Determinants of Insomnia among Mothers during Postpartum Period in Northwest Ethiopia. (1st April 2019) - Belete, Habte; Misgan, Eyaya
Abstract : Objective . Postpartum period is a state of instability that may be accompanied by mood liability, anxiety, insomnia, and neuropsychiatric disturbance in women. This neuropsychiatric disturbance has a negative influence on the child's psychological and physical development. Our aim was to see the level of sleep difficulties among postpartum mothers in three obstetric care settings in Ethiopia. Method . Institutional based cross-sectional study was conducted at one referral hospital and two health centers. A total of 988 postpartum mothers had been interviewed for sleep difficulties by using Athens Insomnia Scale (AIS). Adjusted Odd Ratio (AOR) and 95% Confidence Interval (CI) were used and P-value <0.05 was used for indicating significant variables. Result . The prevalence of sleep difficulty between four to six weeks of postpartum period was 21.8% (215/988). Marital status of divorced/widowed/separated [AOR= 2.29, 95% CI (1.40, 6.08)], no educational opportunity [AOR= 2.35, 95% CI (1.57, 3.51)], having poor social support [AOR=2.82, 95% CI (1.63, 4.88)], alcohol use [AOR=1.58, 95% CI (1.13, 2.22)], history of depression [AOR=1.93, 95% CI (1.13, 3.31)], and who has poor support from husband [AOR=1.94, 95% CI (1.18, 3.18)] had association with sleep difficulty. Conclusion . There is a high magnitude of sleep difficulties during four to six weeks of postpartum period in postpartum mothers and they are associated with many preventable risk factors.